Birken-Wälder : Teil 1: Texte. Teil 2: Apparate und Kommentare. - Garber, Klaus (Neudrucke deutscher Literaturwerke. N.F., 2014)
This volume presents 430 poems and poem groups written by Sigmund von Birken, typically on commission, for bourgeois patrons and members of the city of Nuremberg's patrician class. The first subvolume contains the texts; the second subvolume the philological apparatus and commentaries. The book reveals the activity of a "literary service provider," and will be of interest to historians, theologians, and scholars of cultural and literary studies.